Implementasi Metode Role Play Berbantuan Kahoot Dalam Meningkatkan Hasil Belajar Siswa Pada Pembelajaran Fikih Di Kelas VIID Mts As’adiyah Uloe - Syafi'i, Ahmad; Darnaningsih, (Tasamuh: Jurnal Studi Islam, 2025)
This study aims to describe the improvement of student learning outcomes in learning Fikih material on the Provisions of Makmum Masbuk through the application of the Role Play learning method assisted by Kahoot. The research subjects were students of class VII D MTs As'adiyah Uloe. This study used a classroom action research design (PTK) consisting of two cycles. Data collection was done through observation, tests, and documentation. The results showed that the application of the Kahoot-assisted Role Play learning method can significantly improve student learning outcomes. This is indicated by the increase in student learning outcomes from 60% in the pre-cycle, 80% in cycle I, and 100% in cycle II.